Salvia miltiorrhiza Injection Alleviates LPS-Induced Acute Lung Injury by Adjusting the Balance of MMPs/TIMPs Ratio. (20th July 2020) - Chen, Guobing; Ge, Dandan; Zhu, Bizhen; Shi, Huixuan; Ma, Qilin
Abstract : Salvia miltiorrhiza injection (SMI) is a classical traditional Chinese medicine, which plays an active role in the treatment of many diseases such as promoting blood circulation, removing blood stasis, reducing inflammatory reaction, and improving acute lung injury (ALI). Previous studies have shown that matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are involved in the pathophysiological process of ALI. However, the relationship between SMI and MMPs/TIMPs remains unclear. In this study, Wistar rats were randomly divided into control group (NC), Salvia miltiorrhiza group (SM), lipopolysaccharide group (LPS), and Salvia miltiorrhiza treatment group (Tsm). The four groups were subdivided into four time points (2, 6, 12, and 24 hours), and specimens were collected after animal sacrifice at each time point. Serum TNF- α and IL-6 levels were detected by ELISA. The degree of lung injury was determined by lung tissue hematoxylin-eosin staining, lung wet/dry weight (W/D) ratio, and lung permeability index. The changes in lung MMPs/TIMPs protein and mRNA were detected by Western blot and real-time quantitative PCR. The results showed that rats injected with LPS experience acute lung injury, and the ratio of MMPs/TIMPs in lung tissues increased gradually with time. In the Tsm group, the ratio of MMPs/TIMPs decreased gradually, and likewise, the balance was gradually restored, while indicators related to lung injury were gradually declined. These data suggest that SMI alleviates LPS-induced acute lung injury; this protective effect may be related to regulation of the balance of MMPs/TIMPs ratio.